2008
DOI: 10.1007/s10694-008-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic Performance of Residential Fire Sprinkler Systems

Abstract: A benefit-cost analysis is performed to measure the expected present value net benefits (PVNB) resulting from the installation of a residential fire sprinkler system in a newly constructed, single-family house. The benefits and costs associated with installation and use of a fire sprinkler system are compared across three prototypical single-family house types: colonial, townhouse, and ranch. Each of the house types varies by design, size, and fire sprinkler affordability. Six fire sprinkler system designs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In total, 25 explanatory variables were extracted from several databases, including a variety of socioeconomic attributes according to the results in previous studies [21,[23][24][25][26][27]. These variables not only consider the influence of socioeconomic conditions on fire occurrence but also consider the influence of climate and topographic conditions.…”
Section: Explanatory Variables: Selection and Pre-processingmentioning
confidence: 99%
“…In total, 25 explanatory variables were extracted from several databases, including a variety of socioeconomic attributes according to the results in previous studies [21,[23][24][25][26][27]. These variables not only consider the influence of socioeconomic conditions on fire occurrence but also consider the influence of climate and topographic conditions.…”
Section: Explanatory Variables: Selection and Pre-processingmentioning
confidence: 99%
“…The sprinkler systems, which can directly control or suppress the fire, are very reliable in protecting buildings against fires [1][2][3]. It is also well recognized that smoke and heat vents can play an important role in the fire safety design of buildings besides sprinklers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive effect of the sprinklers, it is not certain that it is economically efficient to install sprinklers in buildings because the cost is too high. Butry (2009) found that installing private homes with sprinklers was economically efficient, whereas a previous study by Harmathy (1988) did not find it profitable. A Swedish cost-benefit study by Juås (1994) used American and Canadian results for the early 80s showing a 44% reduction in deaths and 65% reduction in property damage when sprinkler were used.…”
Section: Evidence Of Sprinkler Efficiencymentioning
confidence: 74%
“…Similar effects to those found by Hall were obtained earlier from US data. Butry (2009) used in his cost-benefit analysis of American sprinklers, effect relationships, derived from data for 2002 to 2005, to show a 100% decrease of fatalities in homes with sprinklers, 57% fewer people with injuries and 32% less property damage. However, smoke detectors were not controlled for.…”
Section: Evidence Of Sprinkler Efficiencymentioning
confidence: 99%